(untitled) (Atti del Sodalizio Glottologico Milanese, 2023)
This paper aims at analysing a case of “polymorphism” in Ancient Venetan dialects, that is the free alternation of (h)abù and (h)abiù in the perfect participle of ‘to have’ attested in XIII-XIV texts of Venice, Padua and Verona. I will treat this alternation as an instance of “overabundance” in order to show that it and similar cases largely attested in Venetan varieties do not represent “canonical” irregularity; on the contrary, they are coherent with diachronic trends and well attested comparatively.